The Effect of Good Corporate Governance and Company Size on The Profitability of Islamic Insurance Companies in Malaysia - Nabihah, Rifdah; Nasution, Zubaidah; Setiawan, Surya (Universitas Siliwangi, 2023)
Introduction to The Problem: The development of Malaysia's financial industry continues to accelerate but it does not rule out the possibility that there are still frequent irregularities in corporate governance.Purpose/Objective Study: The purpose of this research is to analyze the effect of Good Corporate Governance and Firm to Profitability of Sharia Insurance in Malaysia.Â Design/Methodology/Approach: This research uses a quantitative approach using secondary data. The population of this study is Takaful companies in Malaysia with a research period of 2016-2021. The sampling technique used purposive sampling method. Samples that met the criteria were 10 Takaful companies in Malaysia out of a total of 10 Takaful companies in Malaysia. The model used as an analysis tool is multiple linear regression. Data processing in this study uses the SPSS 25 tool.Â Findings: The results of this study indicate that simultaneously the variables of the Board of Commissioners, Sharia Committee, and Company Size have a positive and significant effect on Profitability which is proxied by Return On Assets of Islamic Insurance Companies in Malaysia, while partially the Board Commissioner has a positive and insignificant effect, Sharia Committee has a negative and not significant effect, and Company Size has a positive and significant effect on the profitability of Islamic insurance companies in Malaysia.Paper Type: Research ArticleÂ